Negative Events During Adulthood are Associated With Symptom Severity and Altered Stress Response in Patients With Irritable Bowel Syndrome - Parker, Colleen H. (Clin Gastroenterol Hepatol, 2019)
BACKGROUND & AIMS: Irritable bowel syndrome (IBS) is a stress-sensitive disorder associated with dysregulation of the hypothalamic–pituitary–adrenal pathway. We studied the cumulative effect of events during adulthood on this pathway in patients with IBS. METHODS: We studied 129 patients with IBS, based on Rome III criteria (mean age 28.1 years, 66% women), and 108 healthy individuals (controls; mean age 29.8 years, 60% women) who completed the Life Experiences Survey from August 2013 to September 2017. Data were collected on the presence and effects of events since age 18, IBS severity scores, and IBS-related quality of life. For a subset of subjects, we measured serum cortisol and adrenocorticotropic hormone (ACTH) production in response to administration of corticotrophin-releasing factor and ACTH. RESULTS: Compared with controls, patients with IBS perceived more adulthood life events as negative and had a significantly higher negative life event impact score (14.17±12.04 vs 10.83±9.98; P=.022). In patients with IBS, the presence of more-negatively perceived adulthood life events was associated with worse IBS symptom severity (β=1.53, 95% CI, 0.21–2.84; P=.025) and IBS-related quality of life (β=−0.70; 95% CI, −1.02 to −0.38; P<.001). Negatively perceived adulthood life events were associated with reduced production of ACTH in response to corticotrophin-releasing factor in patients with IBS compared with controls (P<.05). CONCLUSION: In a study of more than 200 subjects, we associated more-negatively perceived events during adulthood with an increased risk for IBS, worse symptom severity and quality of life, and a dysregulated stress response. Understanding the effects of events that cause stress in adults and their perceived effects on IBS may help guide disease management.